2021
DOI: 10.1111/mice.12789
|View full text |Cite
|
Sign up to set email alerts
|

Measuring aggregate morphologies based on three‐dimensional curvature analysis

Abstract: Digital image processing has become the mainstream method for measuring aggregate morphologies. However, the results of the image method are seriously affected by the laying style of aggregates. This study proposes a morphological analysis method based on three‐dimensional curvature analysis. The results show that the values of maximum curvature and standard deviation of Gaussian curvature on the aggregate surface can be used to represent the angularity and texture, respectively. The relative ranking of method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The particle shape is evaluated at various geometric levels. Prior research has identified three key criteria for quantifying particle shape: overall shape, roundness, and surface texture [12,13]. Considering that the surface texture is effectively represented by the friction coefficient value in DEM simulations, and this study aims to capture the wide variety of particle shapes, the overall shape emerges as the most suitable criterion for characterization.…”
Section: Statistical Analysis Of Gravel Shapesmentioning
confidence: 99%
“…The particle shape is evaluated at various geometric levels. Prior research has identified three key criteria for quantifying particle shape: overall shape, roundness, and surface texture [12,13]. Considering that the surface texture is effectively represented by the friction coefficient value in DEM simulations, and this study aims to capture the wide variety of particle shapes, the overall shape emerges as the most suitable criterion for characterization.…”
Section: Statistical Analysis Of Gravel Shapesmentioning
confidence: 99%
“…The asphalt mixture is mainly composed of aggregate and asphalt slurry, which includes asphalt and mineral powder. Although the content of the asphalt slurry in asphalt mixture is small, it plays a key role in the quality of the asphalt mixture [ 14 , 15 , 16 , 17 ]. Fiber asphalt slurry is a mixture of asphalt, fiber, and mineral powder.…”
Section: Introductionmentioning
confidence: 99%